Pure Psychiatric Injury Pursuant to the Civil Liability Legislation: An(other) Economic Perspective - Allcock, Martin (Lawbook Co., 2015)
Despite the enactment of civil legislation affecting claims for pure mental harm in many jurisdictions in Australia, the High Court decision in Wicks v State Rail Authority (NSW) (2010) 241 CLR 60; [2010] HCA 22 has caused some concern that the economic goals underpinning the civil liability legislation will be threatened. In this article, the economic sustainability of the law of negligence with respect to pure mental harm is considered in light of three particular issues. The first is the High Court’s 2015 decision in King v Philcox (2015) 255 CLR 304; [2015] HCA 19 in which the South Australian civil liability legislation was considered. The second is the threat to healthy insurance markets posed by the civil liability legislation itself as a result of inconsistencies between jurisdictions. The third relates to the threat posed by the civil liability legislation to the ability of the law of negligence to achieve economically efficient levels of accident and accident-prevention costs. It is argued that the civil liability legislation is not only well-suited to achieve its primary goal of reducing the social costs of accidents, but may well be a greater threat to that goal than the common law.